ANALISIS UPAYA HUKUM PERDATA TERHADAP PENCEMARAN NAMA BAIK DI MEDIA SOSIAL - NIM. A1011201032, FAISAL (Fakultas Hukum Universitas Tanjungpura, 2024)
Abstract With the development of information technology, especially social media, defamation cases are increasingly in the spotlight before the District Court. case of claim for compensation for unlawful acts based on defamation on social media filed by the plaintiff against the defendant. Whereas in June 2018 there was news that was insulting, defamatory and slanderous about the Plaintiff via electronic media which was spread in the WhatsApp (WA) Group of Management/Members of the Rukun Sinoman Dana Pangrukti Association